2022
DOI: 10.1002/aenm.202200321
|View full text |Cite
|
Sign up to set email alerts
|

Regulating *OCHO Intermediate as Rate‐Determining Step of Defective Oxynitride Nanosheets Enabling Robust CO2 Electroreduction

Abstract: hydrogen storage and formate fuel cells. [5] Notably, a tremendous amount of reports are devoted to exploring the advanced electrocatalysts for formate production through the electrochemical CO 2 reduction reaction (CO 2 RR). Among these catalysts, In-based materials, including oxides, [6][7][8] nitrides, [9] sulfides, [10,11] MOFs, [12][13][14][15] pure metal, [16,17] and singleatom catalysts, [18,19] have attracted extensive attentions owing to their features of high formate selectivity and low toxicity. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 58 publications
(66 reference statements)
4
29
0
Order By: Relevance
“… with strong bonding is more likely to bind to H + to form OCHO* intermediates, which is more conducive to the next reaction of the formation of the formate product. 46–48…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… with strong bonding is more likely to bind to H + to form OCHO* intermediates, which is more conducive to the next reaction of the formation of the formate product. 46–48…”
Section: Resultsmentioning
confidence: 99%
“…CO *À 2 with strong bonding is more likely to bind to H + to form OCHO* intermediates, which is more conducive to the next reaction of the formation of the formate product. [46][47][48] Due to the limitation of the low CO 2 diffusion rate in H-type cells, the current density of specic products makes it difficult to meet the industry standard of 200 mA cm −2 . In this regard, a ow cell with faster CO 2 mass transmission is constructed to study the catalytic activity of the Bi 2 O 2 SO 4 catalyst for CO 2 reduction (Fig.…”
Section: Maximum Fe Hcoomentioning
confidence: 99%
“…Definitions of the figures of merit are explained in Section . The last column shows the icon used to represent each study in the graphical representations of Figures –, according to the symbols and meanings detailed in Table . …”
Section: State Of the Art Of Continuous Electrochemical Co2 Reactors ...mentioning
confidence: 99%
“…10 Studies have shown that C1 is one of the most economical and feasible products for industrialization in the future, and formate can be widely used in textiles, pharmaceuticals, liquid hydrogen carriers, fuel cells and other fields. 11 Therefore, many catalysts such as Sb, 12 In, 13,14 Sn 15 and Bi 16 have been developed and constructed for the electrocatalytic reduction of CO 2 to formate.…”
Section: Introductionmentioning
confidence: 99%